2020
DOI: 10.1111/jppi.12355
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Living Conditions of People with ID: A Follow‐Up after 16 Years

Abstract: Background: The Swedish disability policy has an ambition that people with disabilities should have the possibility to live like everyone else in the community. A study in 2001 described living conditions of people with ID born 1959ID born -1974 in Uppsala County as compared to the general population in the same age group. The results showed differences between the two groups, particularly regarding employment, finances, and social life. Specific Aims: The aim of the present study were to explore changes in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 29 publications
(46 reference statements)
1
11
0
Order By: Relevance
“…Furthermore, in our previous research, we have investigated the health of people with ID and affective or anxiety diagnoses regarding comorbidity, healthcare utilisation and polypharmacy (Axmon et al, 2019;El Mrayyan et al, 2019, 2020. Our results confirmed previous research indicating a great amount of multimorbidity and specialist healthcare among people with ID.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, in our previous research, we have investigated the health of people with ID and affective or anxiety diagnoses regarding comorbidity, healthcare utilisation and polypharmacy (Axmon et al, 2019;El Mrayyan et al, 2019, 2020. Our results confirmed previous research indicating a great amount of multimorbidity and specialist healthcare among people with ID.…”
Section: Introductionsupporting
confidence: 85%
“…Although the former, large care institutions are closed, significant differences remain in the living conditions for people with ID and the general population (Jansson, 2006;Tøssebro et al, 2012). A follow-up study after 16 years concerning living conditions after deinstitutilisation in Sweden found that people with ID lived in more restricted social enviroments, had less leisure time and had a more limited social life compared to the general population (Umb Carlsson, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Studies, both in Sweden and internationally, have compared living conditions of people with and without disabilities (Barranha et al,2021; Emerson et al, 2012; Pérez-Hernández et al, 2019; Umb Carlsson and Sonnander, 2005). Some studies focus on objective living conditions in various domains: housing, occupation, education, finances, leisure, personal safety and social belonging (Umb Carlsson, 2020; Umb-Carlsson and Sonnander, 2005). Other studies pay attention to peoples’ experiences of their everyday lives (cf.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies the living conditions of a selected group of people with intellectual disabilities were reported from a proxy view (Umb Carlsson, 2020; Umb-Carlsson and Sonnander, 2005). In this study, we focus on experienced living conditions from the perspective of adults with intellectual disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Community exclusion may be perpetuated by perceptions of people with intellectual disability as being different, difficult to approach and prone to inappropriate behaviour, although some neighbours are open to engagement ( Overmars-Marx et al, 2018 ). Studies internationally continue to identify limited community participation for people with intellectual disability ( Bredewold, 2021 ; Merrells et al., 2019 ; Umb Carlsson, 2021 ).…”
Section: Introductionmentioning
confidence: 99%